The Implementation of the Broad-Based Black Economic Empowerment (B-BBEE) Policy in South Africa: a Myth or a Reality in SMEs? - Godfrey Tambudzayi Musabayana; Emmanuel Mutambara (Australasian Accounting, Business and Finance Journal, 2022)
The post independent South African government in 1994 started operating in an environment that was characterised by racial discrimination, exclusion of the black majority from the economic activities of their country and were relegated to second class citizens by apartheid. The Black Economic Empowerment (BEE) became the main driver of the South African Government’s effort to overcome the apartheid legacy and was seen as a tool address these imbalances. This article analyses the effects of the Broad-Based Black Economic Empowerment (B-BBEE) policy on the SMEs. This research contributes to the knowledge of African governments on how the indigenous policies can close the gap between the white minority who control the economy and the disadvantaged black majority who have been marginalised by their colonial masters. Methodologically, the study critically analysed the literature of B-BBEE policy and how it has been implemented in South Africa since it was put in place. The researcher drew insights from Black Economic Empowerment (BEE), which was later amended to Broad-Based Black Economic Empowerment (B-BBEE) and the findings of other researchers.
Keywords: apartheid; black empowerment; SME development; indigenous